The Spirit, hermeneutics, and dialogues - Bieringer, R. (Reimund); De Mey, Peter, 1966-; Ibita, Ma. Marilou S.; Pollefeyt, Didier (Annua nuntia Lovaniensia, 2019)
The second half of the 20th century witnessed unprecedented enthusiasm for inner-Christian ecumenical dialogue as well as Christian-Jewish dialogue. However, at the time of the transition from the 20th to the 21st century the dialogues were marked by disillusionment and disappointment due to the fact that not enough progress was experienced with regard to concrete everyday issues. Moreover theoretical points of disagreement remained obstacles for a real mutual understanding, the major ones being the interpretation of certain Biblical passages (esp. John 14:6 and 15:26) and their implications for Christology and the theology of the Trinity. This book explores "new hermeneutics for renewed dialogues." To use a metaphor found in the book, the contributions of this volume are suggesting "new songs" with regard to the dialogues by proposing a future-oriented hermeneutics and a shift from an exclusive focus on Christology to including Pneumatology and thus the doctrine of the Trinity. By so doing the authors and editors intend to offer a new impetus and a new elan in Roman Catholic-Eastern Orthodox as well as Christian-Jewish dialogues. The co-authors of this book contribute pneumatological hermeneutical insights from their respective Protestant, (Christian) Orthodox, Roman Catholic and Jewish perspectives